Individualism and social solidarity in vaccination policy: some further considerations - Fiona M. Sim (BMC, 2017)
Abstract This commentary, in response to the paper by Boas et al [IJPHR December 2016], considers some of the wider ethical, cultural and practical factors that may influence the official response of a polio-free nation following the identification of introduced wild virus within its borders. It looks at factors influencing vaccine uptake internationally, using examples of nations striving to improve childhood vaccine uptake, the relevance of mandatory versus voluntary immunisation and the role of public education and misinformation.